PROFIL DERMATITIS ATOPIK DI POLIKLINIK KULIT DAN KELAMIN RSUP PROF. DR. R.D KANDOU MANADO PERIODE JANUARI 2010 - DESEMBER 2012 - Febriansyah, Juan P. E.; Kapantow, Grace M.; Hariyanto, Agus (UNIVERSITAS SAM RATULANGI, 2015)
Abstract: Atopic dermatitis (AD) is a chronic and recurrent inflammatory disease most commonly found during infancy and childhood. This disease is very complex and has a variety of clinical manifestations. Its management depends not only on the medication, but also on skin care and avoidance of trigger factors. This study aimed to obtain the profile of atopic dermatitis at the Dermatovenerology Clinic of Prof. Dr. R. D. Kandou Hospital Manado period January 2010 to December 2012. This was a retrospective study using medical records of new registered patients at the Dermatovenerology clinic. New cases were grouped according to sex, age, occupation, treatment, and coinfection diseases. The results showed that there were 461 (16.26%) new cases of AD out of 2,835 cases, consisted of 289 (62.69%) females and 172 (37.31%) males with a ratio of 1.7:1. The most frequent age group was >12 years old (58.35%); they were commonly students (43.38%). The most frequent treatment was a combination of oral antihistamin and topical corticosteroid (49.67%). No coinfection was recorded among 332 cases (72.02%). Conclusion: Most of the atopic dermatitis cases at the Dermatovenerology Clinic of Prof. Dr. R. D. Kandou Hospital Manado for the last 3 years were females, age group >12 years old, and as students. Combination of oral antihistamin and topical corticosteroid was the most common treatment. Almost all cases had no coinfection.Keywords: atopic dermatitis, profileAbstrak: Dermatitis atopik (DA) merupakan penyakit peradangan kulit kronis dan residif yang sering terjadi pada masa bayi dan kanak-kanak. Penyakit ini sangat kompleks dengan gambaran klinis bervariasi. Penatalaksanaannya tidak hanya bergantung pada pengobatan, namun juga perawatan kulit dan menghindari faktor pencetus. Penelitian ini bertujuan untuk mendapatkan profil DA di Poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado periode Januari 2010 - Desember 2012. Metode penelitian ini retrospektif dengan menggunakan catatan medik pasien baru di Poliklinik Kulit dan Kelamin tersebut. Kasus baru dikelompokkan menurut jenis kelamin, usia, pekerjaan, pengobatan, dan penyakit penyerta. Hasil penelitian memperlihatkan 461 (16,26%) kasus baru DA dari 2.835 kasus baru, terdiri dari 289 (62,69%) perempuan dan 172 (37,31%) laki-laki dengan rasio 1,7:1. Kelompok usia terbanyak ialah >12 tahun sebesar 269 (58,35%), terbanyak pada pelajar/mahasiswa yaitu 200 kasus (43,38%). Terapi tersering ialah kombinasi antihistamin oral dan kortikosteroid topikal sejumlah 229 kasus (49,67%). Sejumlah 332 (72,02%) kasus tidak disertai penyakit lain. Simpulan: Kasus dermatitis atopik di Poliklinik Kulit dan Kelamin RSUP Prof. Dr. R. D. Kandou Manado selama 3 tahun terakhir tersering pada perempuan, kelompok usia >12 tahun, dan pada pelajar/mahasiswa. Kombinasi anti histamin oral dan kortikosteroid topikal menjadi terapi yang tersering diberikan. Sebagian besar kasus tidak disertai penyakit lain.Kata kunci: dermatitis atopik, profil